2019
DOI: 10.3357/amhp.5300.2019
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Systemic and Pulmonary Circulation to Acute Changes in Gravity and Body Position

Abstract: INTRODUCTION: Changes in gravity or body position provoke changes in hydrostatic pressure in the arterial system and in venous return. Potential asymmetries between left (QLV) and right ventricular (QRV) cardiac output during transient gravity changes were investigated. It was hypothesized that blood volume is temporarily stored in the pulmonary vessels, with amount and duration depending on the level and directions of gravity.METHODS: Eight healthy, male subjects (32 ± 3 yr, 182 ± 7 cm, 82 ± 6 kg) were teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 0 publications
0
13
0
1
Order By: Relevance
“…Levels of downward inertial force can be quantified as gravity (+Gz, also called G force). Hydrostatic pressure produced by G force causes blood to flow toward the lower body region, and hemodynamic parameters are affected in hypergravity environments [2][3][4][5]. If G stress surpasses the tolerance, military aircrew will probably experience visual disturbances and even G-induced loss of consciousness (GLOC) that will extremely threaten the flight safety [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Levels of downward inertial force can be quantified as gravity (+Gz, also called G force). Hydrostatic pressure produced by G force causes blood to flow toward the lower body region, and hemodynamic parameters are affected in hypergravity environments [2][3][4][5]. If G stress surpasses the tolerance, military aircrew will probably experience visual disturbances and even G-induced loss of consciousness (GLOC) that will extremely threaten the flight safety [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Their experiment showed that there is a decreased stimulation of volume receptors in microgravity. Furthermore, a minimal difference between pulmonary blood circulation and systemic blood circulation is seen in response to acute changes in gravity and body position relative to the force of gravity 3 . There are assumptions that there is a transient difference between right and left ventricular ejection fraction in response to acute gravity differences 3 20 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a minimal difference between pulmonary blood circulation and systemic blood circulation is seen in response to acute changes in gravity and body position relative to the force of gravity 3 . There are assumptions that there is a transient difference between right and left ventricular ejection fraction in response to acute gravity differences 3 20 21 . The difference between the ejection fractions of the ventricles and the understanding of the effects of physical pressure (e. g., the Ex-Ex maneuver) on the pulmonary vasculature holds potential for diagnosis and further understanding of the pulmonary vascular disease, e. g. idiopathic pulmonary arterial hypertension (PAH).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies have reported the use of centrifuges for simulation of parabolic flight involving human participants. [4,5] Human Centrifuge, as a simulation modality for parabolic flight, may serve as a training platform for the preparation of space crew for the subsequent actual parabolic flight and space missions by allowing their familiarization and physiological adaptation to such novel environments. The present study was undertaken to evaluate the feasibility of using human centrifuge for parabolic flight simulation.…”
mentioning
confidence: 99%